Effects of voandzou (Vigna subterranea) and spirulina (Arthrospira platensis) enriched biscuits intake on nutritional and stress parameters in young wistar rats - Majesté Mbiada Pahane; Dimitry Yannick Mang; Alain Paul Nanssou Kouteu; Diane Armelle Djouka Ngnang; Danielle Ange Dieukep; Siberbine Sofeu Kamdom; Ashu Michael Agbor; Nicolas Yanou Njintang (Applied Food Research)
The aim of this study was to evaluate the effect of partial substitution of wheat flour by voandzou flour and spirulina powder on the biological properties of biscuits. Thus, five biscuit formulations were produced: standard biscuit, voandzou biscuit (30 %), spirulina biscuit (4 %), spirulina (4 %)+Voandzou (26 and 30 %) biscuits. The chemical composition of these biscuits was evaluated and wistar rats (n = 5/group) were fed with them for 28 days. Protein efficiency ratios (PER and NPER), real (TD) and apparent (AD) digestibility, haematological parameters and in vivo stress were assessed. Biscuit protein ranged from 8.18 to 17.16 %; sugar 62.75–67.21 %, fat 10.12–14.79 %, ash 3.03–4.35 %. Like spirulina powder (4 %), the incorporation of voandzou flour (30 and 26 %) significantly (p < 0.05) increased protein, ash and total phenolic compound content (2.21 to 3.33 mg/100 g DM). Reductions of 3.46 % to 9.75 % in carbohydrates were noted with wheat substitution. By contrast, the latter increased (p < 0.05) the protein digestibility parameters of the biscuits: PER (3.01 to 4.68 g); NPER (1.73 to 2.26 g); TD (82.02 to 91.45 %) and AD (70.11 to 81.33 %). Voandzou and spirulina biscuits improved blood counts in rats. The red blood cell counts (RBC) of the rats varied between 8.12–9.22 × 106/mm3; 13.43–14.98 g/dL for haemoglobin and 46.03–57.12 % for haematocrit levels. The correlations between the levels of MDA-Tannins (r=-0.84, p < 0.05) and total MDA-Phenols (r=-0.78, p < 0.05) show that the phenolic compounds found in biscuits inhibit in vivo lipid oxidation in rats.